Preservice teachers’ beliefs about high-stakes testing and their working environments - Sharon L. Nichols; Shon Brewington (Education Policy Analysis Archives, 2020)
In this exploratory mixed methods survey study, we assess preservice teachers’ (n=379) experiences with and beliefs about their high-stakes testing experiences and analyze how they relate to their beliefs about the role and efficacy of high-stakes testing in education and their future profession. Using Likert, vignette, and open-ended response opportunities, we gauged preservice teachers’ beliefs about accountability and the role of high-stakes testing in three ways: (a) what are their personal experiences with high-stakes testing, (b) what are their their beliefs about accountability and high-stakes testing in general, and (c) what role does accountability (and testing pressures) play in their future workplace preferences? Results indicate that preservice teachers’ experiences with and beliefs about high-stakes testing accountability vary based on gender, ethnicity, and previous experiences with high-stakes tests. Importantly, although in aggregate our participants reported they generally disliked the high-stakes tests they personally had to take in high school, subgroup analyses reveal that for those who took them during the NCLB era, they also saw high-stakes tests as good thing for education overall. Preservice teachers who were younger and “grew up” under NCLB and the height of high-stakes testing believed high-stakes tests to be a waste of time for them personally, but a useful way to evaluate teachers as an educational policy. Vignette and qualitative analyses of workplace preferences and rationales underscore some of the assumptions our preservice teachers hold about high-stakes testing as a policy mechanism to help explain this finding. We conclude with implications for policy and future research.